PREFCLIM: A high-resolution mixed-layer climatology of the eastern tropical Atlantic - Willi Rath; Marcus Dengler; Jan Lüdke; Sunke Schmidtko; Michael Schlundt; Peter Brandt; Karl Bumke; Marek Ostrowski; Anja K van der Plas; Tim Junker; Volker Mohrholz; Abdoulaye Sarre; et al. (PANGAEA, 2016)
PREFCLIM is a mixed-layer climatology for the Eastern Tropical Atlantic. The climatology contains a high-resolution (0.25 degrees) monthly-mean mixed-layer hydrography (mixed-layer depth, temperature, salinity), and coarse-resolution (2.5 degrees) estimates of the mixed-layer heat and salt balance, as well as of near-surface velocities and of air-sea fluxes. All existing hydrographic products of the region were hampered by the sparse availability of near-shore data owned by the West-African coastal countries, which could, however, be included in the new climatology.